2020
DOI: 10.5114/pg.2020.99041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gastric acidity by short-duration intragastric pH-monitoring with standardised breakfast in functional and some other dyspepsias

Abstract: Introduction Preliminary assessment of gastric secretion in the treatment of organic and functional dyspepsia may offer advantages over the empirical administration of proton pump inhibitors suggested by most clinical guidelines. Aim To develop a simplified pH-metric test with standardised meal, and on its basis to perform an assessment of the functional state of gastric secretion in the most common dyspepsias. Material and methods Serum peps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Melewatkan atau tidak mengonsumsi sarapan dapat menjadi bagian dari kebiasaan makan yang tidak teratur, di mana seseorang mengonsumsi makanan secara berlebihan pada waktu tertentu atau bahkan tidak makan sama sekali pada waktu yang lain. Pola makan yang tidak konsisten seperti ini dapat berdampak pada keseimbangan asam lambung dan berperan dalam timbulnya sindrom dispepsia (Melashchenko, 2020).…”
Section: Pembahasan Hubungan Sarapan Pagi Dengan Sindrom Dispepsiaunclassified
“…Melewatkan atau tidak mengonsumsi sarapan dapat menjadi bagian dari kebiasaan makan yang tidak teratur, di mana seseorang mengonsumsi makanan secara berlebihan pada waktu tertentu atau bahkan tidak makan sama sekali pada waktu yang lain. Pola makan yang tidak konsisten seperti ini dapat berdampak pada keseimbangan asam lambung dan berperan dalam timbulnya sindrom dispepsia (Melashchenko, 2020).…”
Section: Pembahasan Hubungan Sarapan Pagi Dengan Sindrom Dispepsiaunclassified
“…Another factor that can impair gastric accommodation is increased duodenal acid exposure, probably through triggering duodeno-gastric reflexes [102,103]. Though studies suggest normal acid production in FD patients [104] and only an increase in the duodenal acid exposure due to slow motility, or impaired mucosal barrier, there are other studies which suggest increased acid production as well in a subset of patients [105].…”
Section: Possible Role Of Yoga In Gastric Accommodationmentioning
confidence: 99%
“…Reduced anti-nociceptive role of the vagus nerve [110], corticosterone-induced increased excitability of dorsal root ganglion neurons [66,111], increased acid secretion [105] or increased acid exposure decreased due to slow gastroduodenal motility [112], as well as altered CNS pain processing [22,113] are implicated in gastric hypersensitivity.…”
Section: Possible Role Of Yoga In Gastric Hypersensitivitymentioning
confidence: 99%
“…[136] Instillation of hydrochloric acid into the stomach of healthy subjects induced FD-like symptoms. [137] Some studies have focused on the application of some gastric acid inhibition such as H 2 -receptor antagonists and proton pump inhibitors (PPIs). [138,139] However, these studies showed the opposite results.…”
Section: Excess Gastric Acidmentioning
confidence: 99%